Anti-angiogenic effects of chemotherapeutic agents and their enhancement with OT-515 and S-NACH - Heikal, Shimaa Adel (AUC Knowledge Fountain, 2021)
Chemotherapeutic agents have been used for the treatment of numerous types of tumors with great success. Cisplatin and Doxorubicin are among the well-known chemotherapeutic drugs that showed efficacy against various types of cancers. However, cell resistance and major side effects like chemotherapy-induced peripheral neuropathy (CIPN) are limiting factors in using these compounds. Using a combination or adjuvant compounds with anti-angiogenic effects is one of the strategies suggested to decrease resistance or ameliorate chemotherapeutic toxicity. The present study investigated the anti-angiogenic effects of Cisplatin and Doxorubicin alone and combined with Sulfated non-anticoagulant heparin (S-NACH), a low molecular weight heparin LMWH that has anti-angiogenic and anti-tumor properties, or OT-515, a tempol congener-derived molecule that might act on inhibiting tumor proliferation and angiogenesis. The compounds' ability to enhance the effects of chemotherapeutic agents and decrease the doses used was tested in-vitro and in-vivo through using a chick chorioallantoic membrane (CAM) model, in the presence and absence, of tumor cells. To elucidate the mechanism of anti-angiogenic effect of the compounds, their impact on endothelial cells was studied by performing cytotoxicity assays using HUVEC and mouse endothelial cells. The results showed that combinations of Cisplatin and Doxorubicin with S-NACH or OT-515 had enhanced anti-tumor and anti-angiogenic effects than individual treatments. This suggests that OT-515 and S-NACH provide promising adjuvant therapy to reduce doses of traditional chemotherapeutic agents and ameliorate their adverse effects.